Evaluating the Impact of Geometric Dimensions of a Multi-Split Ring Resonator - FADHIL, TAMARA; Murad, Noor Asniza; Hamid, Mohamad Rijal (ELEKTRIKA- Journal of Electrical Engineering, 2024)
In this paper, a metamaterial unit cell is designed and simulated based on the concept of multiple split-ring resonators (SRRs) in a compact size. The presented nested modified SRR resonator construct has the advantage of achieving more usable split gaps by increasing capacitance, resulting in a lower operational resonance frequency and improved sensitivity over typical SRR metamaterials. The impact of several split ring resonator geometric characteristics, such as the gap space, the width of the copper lines, the inner rings length, and the outer ring length on magnetic permeability and permittivity was analyzed. The modified metamaterial can be utilized for 5G mobile applications.